PENGEMBANGAN BUKU SAKU DIGITAL BERBASIS CANVA PADA MATERI ALJABAR UNTUK KELAS VIII SMP NEGERI 6 MERANGIN - Warih Ismita Dewi; Muhammad Jainuri; Yohanes (Hira Institute, 2024)
The media used at SMP Negeri 6 Merangin still uses package books, so the learning process is not interactive. This research is research and development (R&D). The development model used in research on e-pocked book based canva is ADDIDE, which was validated by five validators. Validity is reviewed from validation sheet. Practicality is reviewed from e-pocked practicality questionnaire sheet and student interviews. Meanwhile, effectiveness is reviewed from the activities of students and the learning outcomes of students after using e-pocked based canva. The results of the data analysis show the average score of validation results by material experts at 4.34 with a very valid category, Indonesian language experts at 4.73 with a very valid category, media experts at 4.27 with a very valid category, and teacher validation at 4.55 with a very valid category. The average overall score of the validators was 4.47, with a very valid category. The percentage of practicality questionnaire responses was 79% in the practical category. The average percentage of effectiveness of learning outcomes is 90.62% with an effective category, and the percentage of student activity is 83.58% with a very effective category. Based on these results, it is found that the research that has been developed is valid, practical, and effective